Moving Object Detection on CCTV Surveillance Using the Frame Difference Method - Saluky Saluky (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2019)
In today's computer vision research, many build systems for observing humans and understanding their appearance, activities, and behaviour that provide sophisticated interfaces for interacting with humans, and create plausible human models for various purposes. This paper presents a simple algorithm for detecting moving objects from a static background based on frame differences. First, the first frame is captured via a static camera such as Closed Circuit Television (CCTV) after which a sequence of frames is taken periodically. Second, the absolute difference is calculated between successive frames and the difference in images is stored in the system. Third, the difference image is converted into a grey image and then translated into a binary image. Finally, morphological filtering is carried out to remove noise. In the last process, moving objects can be detected in conditions that do not change much apart from moving objects.